2013
DOI: 10.1007/s00401-013-1165-y
|View full text |Cite
|
Sign up to set email alerts
|

Integrative genetic, epigenetic and pathological analysis of paraganglioma reveals complex dysregulation of NOTCH signaling

Abstract: Head and neck paragangliomas, rare neoplasms of the paraganglia composed of nests of neurosecretory and glial cells embedded in vascular stroma, provide a remarkable example of organoid tumor architecture. To identify genes and pathways commonly deregulated in head and neck paraganglioma, we integrated high-density genome-wide copy number variation (CNV) analysis with microRNA and immunomorphological studies. Gene-centric CNV analysis of 24 cases identified a list of 104 genes most significantly targeted by tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(63 citation statements)
references
References 69 publications
(101 reference statements)
0
60
1
2
Order By: Relevance
“…Biological process analysis revealed that these 77 genes, activated by both TRIM28 and EZH2, share GO functions of cell projection, morphogenesis and development that are associated with stem cells and metastasis (Figure 2e and Supplementary Table S7). Examination of breast cancer patient data, available for 65 of the 77 TRIM28/EZH2-activated genes, show that altered expression of the 65 co-activated genes, 62 of which exhibit gene amplification, 3032 is correlated with a poor probability of overall survival for breast cancer patients with invasive carcinomas (Figure 2f). …”
Section: Resultsmentioning
confidence: 99%
“…Biological process analysis revealed that these 77 genes, activated by both TRIM28 and EZH2, share GO functions of cell projection, morphogenesis and development that are associated with stem cells and metastasis (Figure 2e and Supplementary Table S7). Examination of breast cancer patient data, available for 65 of the 77 TRIM28/EZH2-activated genes, show that altered expression of the 65 co-activated genes, 62 of which exhibit gene amplification, 3032 is correlated with a poor probability of overall survival for breast cancer patients with invasive carcinomas (Figure 2f). …”
Section: Resultsmentioning
confidence: 99%
“…Primary HNPGL cell cultures were established as previously described [6] from two prospectively sampled tympano-jugular HNPGL patients (PTJ64 and PTJ86) carrying the SDHC c.43C>T (p. Arg15*) and SDHD c. 27delC (p. Val10Phefs*5) mutations, respectively. For mutational analysis the coding regions and exon–intron boundaries of SDHB , SDHC and SDHD genes were amplified by PCR as previously described [6, 21, 22].…”
Section: Methodsmentioning
confidence: 99%
“…For mutational analysis the coding regions and exon–intron boundaries of SDHB , SDHC and SDHD genes were amplified by PCR as previously described [6, 21, 22]. PCR products were subjected to 2% agarose gel electrophoresis with ethidium bromide staining and subsequently sequenced using a genetic analyzer (ABI PRISM 310; Applied Biosystems, Milan, Italy).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We recently demonstrated that NOTCH signaling, a fundamental molecular pathway implicated in stem cells maintenance, organogenesis, and carcinogenesis, is commonly activated in head and neck paragangliomas (47). This could have therapeutic implications because it has been shown that NOTCH signaling promotes radioresistance in glioma cells (48).…”
Section: Mechanism Of Action Remains Unclearmentioning
confidence: 99%